Analisis Kandungan Free Fatty Acid (FFA) dan Viskositas Limbah Minyak Jelantah pada UMKM di Kota Malang sebagai Upaya Pengendalian Mutu Bahan Baku Biodiesel - Ahmad Setyo Putra; Areta Triani Putri; Aswangga Bhagas Ramadhan (Fakultas Teknik, Universitas Muhammadiyah Prof. Dr. Hamka, Jakarta, 2025)
This research aims to analyze the Free Fatty Acid (FFA) content and viscosity of waste cooking oil (WCO) generated by small and medium enterprises (SMEs) in Malang City as part of quality control for biodiesel feedstock. Sixty oil samples were tested using the alkalimetric titration method for FFA and a Brookfield viscometer for viscosity measurement. The results showed an average FFA value of 1.38% (ranging from 0.07% to 7.46%) and an average viscosity of 31.28 cP (ranging from 22.75 to 42.13 cP). Most samples met the safe limit (<2%) for direct base-catalyzed transesterification, while approximately 25% required a pre-esterification process. The Pearson correlation indicated a weak but significant negative relationship (r = -0.2898; p < 0.05), suggesting that FFA and viscosity must be controlled independently. These findings highlight the importance of implementing a simple quality control system at the SME level to support sustainable biodiesel production.